Waterproofing of 3D printed concrete - Nienaber, Linda (Stellenbosch : Stellenbosch University, 2025)
Nienaber, L. 2025. Waterproofing of 3D printed concrete. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/1c802bc0-145d-4122-ab4e-de8b4bd08154